Development of Numeracy, Writing, Listening, and Speaking Literacy Assessment Models for Elementary School Students in Makassar City - Nasiruddin, Fathimah Az.zahra; Basri, Syamsurijal; ., Jainuddin; Umar, Muh. Fitrah Ramadhan; Rizal, A. (Journal of Ecohumanism, 2024)
The purpose of this study was to identify the current conditions of numeracy, writing, listening, and speaking literacy assessments in elementary schools, develop a local wisdom-based literacy assessment model that is appropriate for elementary school students, and test the effectiveness of the local wisdom-based assessment model in improving students' literacy skills. The method used is research and development (R & D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The result show that total overall indicator of the effectiveness of improving the previous assessment results of 81.86 with a good category, there was an insignificant increase with a total score of 82.98 which is also in the good category. Based on the results of the development of the local wisdom-based literacy assessment model for numeracy, writing, listening, and speaking in Elementary School students in Makassar City, improvements and revisions need to be made to improve the quality of the assessment, especially literacy and numeracy skills in Elementary Schools.